Group‐Velocity‐Controlled and Gate‐Tunable Directional Excitation of Polaritons in Graphene‐Boron Nitride Heterostructures (Laser Photonics Rev. 12(5)/2018). Issue 5 (May 2018) - Jiang, Yuyu; Lin, Xiao; Low, Tony; Zhang, Baile; Chen, Hongsheng
Abstract : Nano‐Photonics Infrared van der Waals heterostructures for actively tunable near field directionality at the nanoscale. In article number1800049, Xiao Lin, Baile Zhang, Hongsheng Chen, and co‐workers design graphene‐hexagonal boron nitride heterostructures to flip the sign of group velocity of the highly squeezed polaritons in a flexible way, simply through tuning the chemical potential of graphene. This mechanism may promise versatile platforms for reconfiguring the near field light‐matter interaction on‐the‐fly.